PENGARUH PENEMPATAN TUGAS TERHADAP MOTIVASI KERJA PEGAWAI PADA KPPBC TMP BELAWAN - Sumiati, Sumiati; Rangkuti, Sahnan (Journal Economic Management and Business, 2024)
This study aims to determine the effect of job placement on employee motivation at KPPBC TMP Belawan. Using a sample of 65 employees and simple linear regression analysis with SPSS, the results show that job placement has a significant effect on work motivation (significance value 0.001 < 0.05, t_calculated = 8.825 > t_table = 1.669). The coefficient of determination indicates an influence of 55.3%. However, employee rotation has not been carried out regularly or evenly. Therefore, it is recommended that the rotation system be implemented routinely and fairly to enhance motivation and prevent internal conflicts.